Former à l’interdisciplinarité via l’intégration du design à la gestion de projet : apports et limites dans une école d'ingénieurs - Emilien Jacob; Florian Magnani (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Interdisciplinarity is the subject of much scientific and theoretical interest. Although it is often advocated by institutional players, successful examples are rare in the literature. This article presents the results of a 3-year study on a model for interdisciplinary training in project management and design at an engineering school. The aim of the model presented, reinforced by the triangulation of feedback from students, participating teachers and teachers in charge of the approach, is to highlight the contributions and limitations of the training put in place. The limits and prospects will enable us to transfer the approach implemented to other establishments, or to inspire similar approaches.